Analisis Oligopoli pada Industri Telekomunikasi di Indonesia : (Studi Kasus PT Telkomsel Tbk dan PT Indosat Tbk) - Kania Sukma ‘Aadilah Effendi Putri; Naerul Edwin Kiky Aprianto; Maisa Ahallah Nur Aminah; Windiarti Inayah; Farah Shodiqotun Al Muharromah (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze the practice of oligopoly in the telecommunications industry in Indonesia, specifically between PT Telkomsel Tbk and PT Indosat Tbk. The background of this research is the majority share ownership by Temasek in two major telecommunications operators in Indonesia, namely PT Telkomsel Tbk and PT Indosat Tbk, which collectively control approximately 75% of the shares in these two companies. This study employs a qualitative method with a descriptive qualitative approach, using primary data from books, journals, articles, and other library sources as secondary data. The findings of this study indicate the existence of oligopoly practices in the telecommunications industry in Indonesia conducted by Temasek through PT Telkomsel Tbk and PT Indosat Tbk.